(untitled) (Fiep Bulletin - online, 2011)
The rehabilitation of patients with spinal cord injury (SCI) is important for the development of functional independence and return to activities of daily living. The goal this research was to compare the physical fitness level from parathletes and sedentary groups with SCI that had and had not follow-up physiotherapy. The sample included 10 parathletes and 5 sedentary with SCI. The following measurements were performed: muscle strength and resistance in the prone rising trunk, sitting and rising, goniometry in flexion and extension of trunk, skinfolds of triceps, biceps, pectoral and abdomen, but also, blood pressure. The results showed that parathletes had the muscle strength and resistance, range of motion higher than sedentary control group (P<0,05). The skinfods and systolic blood pressure of parathletes were smaller than spinal cord injury sedentary control group (P<0,05), however, diastolic blood pressure did not modify between groups (P>0,05). We conclude that spinal cord injury parathletes have higher physical fitness and lower risk of developing cardiovascular and osteomuscular disease than spinal cord injury sedentary.